Citrus fruit farmers’ adaptation capacities to climate variability in Ngora district, Eastern Uganda - Simon Peter, Achuu; Sarah, Nachuha; Joweria, Nakizito; Henry Musoke, Semakula; Hosea Enos, Opedes (Kabale University Interdisciplinary Research Journal (KURJ), 2022)
Over the past three decades the government of Uganda prioritized fruits growing in Teso sub-region as a means to promote socioeconomic development. However, climate variability threatens the realization of this initiative and yet inadequate research has been done to address this gap. This study assessed citrus fruit farmers’ adaptation capacities to climate variability in Ngora district, eastern Uganda. Longitudinal and cross-sectional research designs were adopted in which 135 randomly selected farmers were interviewed. Findings indicated that 82% of the respondents attested that rainfall amounts and temperature patterns had changed with the highest rainfall of 1686 mm received in 1991, and the lowest amount of 785mm received in 2009. Average annual temperatures in the same period varied between 23.8ºC and 25.7ºC. These variations contributed to a drop in orange fruit yields from 90% in 2015 to below 54% in 2016. Overall, 94.8% of citrus farmers were aware of the term climate variability and they associated it to variation in rainfall amounts and distribution, rise in surface temperature and occurrence of droughts; 73.3% of the farmers had positive attitude towards climate variability adaptation especially in instances where it directly affected their livelihoods. Only 21% of the farmers did something to adapt to climate variability through irrigating young orange trees. Conclusively, citrus growing provided an option to poverty eradication, however climate variability threatens farmer’s efforts. In a short-run farmers may be encouraged to work in groups. Overall capital investment on irrigation technology by government and or other stakeholders will offer lasting solution